Dynamics of the anaerobic threshold of ski racers throughout the annual training cycle - N. Varlamova; T. Loginova; I. Garnov; N. Timofeev; E. Boyko (National Electronic Information Consortium (NEICON), 2020)
To study the dynamics of cardiorespiratory parameters in the anaerobic threshold zone of ski racers throughout the annual training cycle. Materials and methods: 300 examinations of 49 professional ski racers of I category and candidate masters of sports (aged from 15 to 32 years, mean age - 19,7±1,3 (M±m)) were carried out in the breath-by-breath mode on an Oxycon Pro ergospirometric system (Erich Jaeger). Maximal oxygen consumption (MOC: absolute and per kilogram of body weight) was detected during pass-fail test. Heart rate (HR), oxygen consumption (VO2), oxygen pulse and maximal load were registered in the anaerobic threshold zone. Difference between the actual and theoretically calculated HR, VO2 percentage (relate to maximal oxygen consumption) was calculated. Results: pulse increase in the anaerobic threshold zone by 20% prolonged aerobic activity of ski racers and increased maximal aerobic load by 20%. Conclusions: the most favorable values of cardiorespiratory parameters were registered during the preparation period, and the least - during the competition period. This fact requires correction of the training process and rehabilitation.